Pengaruh Perceived Ease of Use Terhadap Online Shopping Intention dengan Perceived Value sebagai Mediasi - Mirza Rizaldi; Mulyono Mulyono; Choirul Anam (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to examine the effect of Perceived Ease of Use on Online Shopping Intention with Perceived Value as a mediating variable among Tokopedia users. A quantitative explanatory method was employed, analyzing data from 110 respondents using Partial Least Square-Structural Equation Modeling (PLS-SEM). The findings revealed that Perceived Ease of Use positively and significantly influences Online Shopping Intention; Perceived Ease of Use significantly influences Perceived Value;Perceived Value positively influences Online Shopping Intention; and Perceived Value partially mediates the relationship between Perceived Ease of Use and Online Shopping Intention. These results support the Technology Acceptance Model (TAM), highlighting the importance of ease of use and Perceived Value in enhancing Online Shopping Intention. Recommendations include optimizing interface design, transaction efficiency, and service reliability to improve user experience in online shopping.